Frequency of Deep Venous Thrombosis in Hospitalized Patients - Ahmad, Waqas; Alamgir, Wasim; Rashid, Amir; Azeem Dar, Abdul Rehman; Kayani, Bilal Ahmed; Zainab, Azka (Pakistan Armed Forces Medical Journal, 2026)
Objective:  To determine the occurrence of deep vein thrombosis (DVT) among hospitalized patients.Study Design: Prospective observational studyPlace and Duration of Study: Pakistan Emirates Military Hospital Rawalpindi, Pakistan from Jul to Dec 2022.Methodology: Hospitalized patients, aged 12-70 years with different medical conditions and suspicion for DVT were enrolled in the study. Venous Doppler ultrasonography was used to detect deep vein thrombosis. Patients having recent surgical procedure or trauma within the previous three months were not included. The continuous variables including age, weight and number of days in the hospital, were summarized by calculating means and standard deviations. Statistical comparisons between deep venous thrombosis negative and deep venous thrombosis positive patients were performed using the Chi-Square test.Results: The study included 275 patients in total, out of which 236(86%) were males and 39(14%) females. Ultrasound examination was done for the recruitment of deep venous thrombosis-positive 125(45%) and negative 150(55%) patients. Patients were also divided by clinical presentation. Most of the deep venous thrombosis-positive patients had malignancy/cancer 43(34.4%), nephrotic syndrome 16(12.8%), and paralysis 13(10.4%).Conclusion: Patients with increased age, prolonged hospital stay, history of malignancy or nephrotic syndrome and prolonged immobilization were found to be at increased risk for deep venous thrombosis, it is recommended that such patients should be considered for deep venous thrombosis prophylaxis with a proper and effective dosage of anticoagulant after weighing risk versus benefit ratio in high risk cases.